STUDYING THE PHYSICAL AND CHEMICAL PROPERTIES OF BIOSAS - Asamatdinov, A.; Kurbanbayeva, A. (SCIENCE and SOCIETY, 2026)
The physicochemical properties of the identified microorganism Bacillus sp., which is an effective producer of biologically active substances, obtained during growth on both hydrophilic and hydrophobic substrates, were studied. It has been shown that when Bacillus sp. grows on glucose, endo-bioSASs associated with cell membrane bacteria are formed. Studies have also been conducted on the electrical conductivity and viscosity of the obtained cultures.